Balloon-Catheter Buddy Technique for Coiling of Very Small Aneurysm - Bhatia, Vikas; Hosur, Bharat; Kumar, Ajay (Journal of Clinical Interventional Radiology ISVIR, 2021)
The catheter movement and stability in coiling of very small aneurysms is challenging. We describe a technique for controlled catheter movement and successful coiling of a very small aneurysm.
Keywords: coiling; very small aneurysms; catheter